Stress Conditions Modulate the Chromatin Interactions Network in Arabidopsis - Yadav, Vikash Kumar; Singh, Swadha; Yadav, Amrita; Agarwal, Neha; Singh, Babita; Jalmi, Siddhi Kashinath; Yadav, Vrijesh Kumar; Tiwari, Vipin Kumar; Kumar, Verandra; Singh, Raghvendra; Sawant, Samir Vishwanath (Frontiers in Genetics, 2022)
Stresses have been known to cause various responses like cellular physiology, gene regulation, and genome remodeling in the organism to cope and survive. Here, we assessed the impact of stress conditions on the chromatin-interactome network of Arabidopsis thaliana. We identified thousands of chromatin interactions in native as well as in salicylic acid treatment and high temperature conditions in a genome-wide fashion. Our analysis revealed the definite pattern of chromatin interactions and stress conditions could modulate the dynamics of chromatin interactions. We found the heterochromatic region of the genome actively involved in the chromatin interactions. We further observed that the establishment or loss of interactions in response to stress does not result in the global change in the expression profile of interacting genes however, interacting regions (genes) containing motifs for known TFs showed either lower expression or no difference than non-interacting genes. The present study also revealed that interactions preferred among the same epigenetic state (ES) suggest interactions clustered the same ES together in the 3D space of the nucleus. Our analysis showed that stress conditions affect the dynamics of chromatin interactions among the chromatin loci and these interaction networks govern the folding principle of chromatin by bringing together similar epigenetic marks.